Evolutionary active transposable elements in the genome of the coelacanth. Issue 6 (1st August 2013) - Chalopin, Domitille; Fan, Shaohua; Simakov, Oleg; Meyer, Axel; Schartl, Manfred; Volff, Jean‐Nicolas; Amemiya, Chris; Meyer, Axel
ABSTRACT The apparent morphological stasis in the lineage of the coelacanth, which has been called a "living fossil" by many, has been suggested to be causally related to a slow evolution of its genome, with strongly reduced activity of transposable elements (TEs). Analysis of the African coelacanth showed that at least 25% of its genome is constituted of transposable elements including retrotransposons, endogenous retroviruses and DNA transposons, with a strong predominance of non‐Long Terminal Repeat (non‐LTR) retrotransposons. The coelacanth genome has been shaped by four major general bursts of transposition during evolution, with major contributions of LINE1, LINE2, CR1, and Deu non‐LTR retrotransposons. Many transposable elements are expressed in different tissues and might be active. The number of TE families in coelacanth, but also in lungfish, is lower than in teleost fish, but is higher than in chicken and human. This observation is in agreement with the hypothesis of a sequential elimination of many TE families in the sarcopterygian lineage during evolution. Taken together, our analysis indicates that the coelacanth contains more TE families than birds and mammals, and that these elements have been active during the evolution of the coelacanth lineage. Hence, at the level of transposable element activity, the coelacanth genome does not appear to evolve particularly slowly. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 322–333, 2014. © 2013 Wiley Periodicals, Inc.